Sudden infant death syndrome as a result of thymic-lymphatic dysgenesis - Saule Amangeldievna Mussabekova; Elena Igorevna Burkova; Kristina Ergardovna Dobler; Balzhan Smailovna Muldasheva; Zhan Zhumagulovich Atmtaev (National Scientific Medical Center, 2024)
Sudden infant death syndrome is one of the leading causes of post-neonatal mortality. The thymic-lymphatic condition in children is a clinically rare manifestation and difficult to diagnose condition, assessed as a background, realized in a number of cases of sudden death syndrome. However, the clinical and histopathological manifestations of thymic-lymphatic status may not be clearly expressed. We present an unusual case of sudden infant death syndrome as a result of thymic-lymphatic dysgenesis complicated by acute adrenal insufficiency.